PENGARUH LAMA PAPARAN LAYAR DIGITAL TERHADAP KEJADIAN SINDROM MATA KERING PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH ANGKATAN 2022 - Haves Ashan; Tri Puspita Prihatinningrum AF; Ibnu Khalid Alfarel (Nusantara Hasana Journal, 2026)
The concept of lifelong learning requires medical students to continuously read and update their medical knowledge, which inevitably increases the use of electronic devices such as computers, tablets, and smartphones. Prolonged use of these devices, along with other close-distance visual habits, elevates the risk of radiation absorption by the eyes. The radiation generates heat on the ocular surface, leading to excessive tear evaporation and consequently increasing the risk of dry eye syndrome. Digital screen exposure for long durations (≥4 hours/day) has been associated with a 70.8% increase in the severity of dry eye syndrome, and such exposure is strongly linked to the occurrence of this condition due to the accumulation of radiation energy absorbed by the eyes during electronic device use. This study aimed to determine the effect of digital screen exposure duration on the incidence of dry eye syndrome among medical students at Baiturrahmah University, Class of 2022. An analytical observational method with a cross-sectional design was employed, using primary data collected from 67 respondents. Univariate analysis was presented as frequency distributions, while bivariate analysis was conducted using Fisher’s Exact Test with a Monte Carlo approach. The results showed that 51 students (76.1%) were categorized as having high digital screen exposure, while 32 students (47.8%) experienced severe dry eye syndrome and 21 students (31.3%) had moderate dry eye syndrome. Statistical analysis demonstrated a significant effect of digital screen exposure duration on the incidence of dry eye syndrome among medical students, with a p-value of 0.006 (p < 0.05). In conclusion, prolonged digital screen exposure significantly influences the incidence of dry eye syndrome among medical students at Baiturrahmah University, Class of 2022.